NUTRITION IN THE TRAINING OF STUDENT-ATHLETES - Ryskin, Petr; Fagina, Stanislava; Shuraleva, Natalia (Revista Inclusiones, 2020)
The relevance of the study is due to the need to solve pedagogical problems of ensuring the cohesion of the sports team in preparation for the competition. The purpose of the study is to assess the awareness of students-athletes about the rules of rational nutrition. The study was conducted at the Department of Physical Education and Sport of the Ural State Economic University in the period 2017-2019. The information base of the study consists of surveys of 56 students professionally engaged in various sports. The research methodology is based on the survey method and subsequent statistical processing of data. The results show that the majority of student-athletes are aware of the basic principles of rational nutrition, but not all follow them, which leads to an increase in the percentage of body fat and a deficiency of vitamins and microelements.